Immune response after oral immunization of goats and foxes with an NDV vectored rabies vaccine candidate. - Magdalena Murr; Conrad Freuling; David Pérez-Bravo; Christian Grund; Thomas C Mettenleiter; Angela Römer-Oberdörfer; Thomas Müller; Stefan Finke (Public Library of Science (PLoS), 2024)
Vaccination of the reservoir species is a key component in the global fight against rabies. For wildlife reservoir species and hard to reach spillover species (e. g. ruminant farm animals), oral vaccination is the only solution. In search for a novel potent and safe oral rabies vaccine, we generated a recombinant vector virus based on lentogenic Newcastle disease virus (NDV) strain Clone 30 that expresses the glycoprotein G of rabies virus (RABV) vaccine strain SAD L16 (rNDV_GRABV). Transgene expression and virus replication was verified in avian and mammalian cells. To test immunogenicity and viral shedding, in a proof-of-concept study six goats and foxes, representing herbivore and carnivore species susceptible to rabies, each received a single dose of rNDV_GRABV (108.5 TCID50/animal) by direct oral application. For comparison, three animals received the similar dose of the empty viral vector (rNDV). All animals remained clinically inconspicuous during the trial. Viral RNA could be isolated from oral and nasal swabs until four (goats) or seven days (foxes) post vaccination, while infectious NDV could not be re-isolated. After four weeks, three out of six rNDV_GRABV vaccinated foxes developed RABV binding and virus neutralizing antibodies. Five out of six rNDV_GRABV vaccinated goats displayed RABV G specific antibodies either detected by ELISA or RFFIT. Additionally, NDV and RABV specific T cell activity was demonstrated in some of the vaccinated animals by detecting antigen specific interferon γ secretion in lymphocytes isolated from pharyngeal lymph nodes. In conclusion, the NDV vectored rabies vaccine rNDV_GRABV was safe and immunogenic after a single oral application in goats and foxes, and highlight the potential of NDV as vector for oral vaccines in mammals.